Market Dominance in Indonesia’s Islamic Banking: Critical Analysis From an Industrial Organisation Perspective - Zaini, Faizi; Kusuma, Airlangga Surya Kusuma (Journal of Finance and Islamic Banking, 2024)
The merger of Bank Syariah Indonesia (BSI) has resulted in the formation of a substantial Islamic bank capable of effectively competing with large conventional banks. Despite this, concerns have been raised that BSI might eliminate smaller Islamic banks. This study aims to critically analyze the characteristics of market dominance in Indonesia's Islamic banking industry before and after the merger of BSI from an industrial organization perspective. We utilized several indicators, including the Concentration Ratio (CR), Herfindahl–Hirschman Index (HHI), and Melnik ratio. The findings strongly indicate market dominance in the Islamic banking industry following the BSI merger. However, we argue that the market dominance achieved by BSI fosters a positive environment by reducing fragmentation within the industry. This merger has also prompted other conventional banks to optimize their support for Islamic banks. Additionally, BSI has the potential to drive the Islamic banking industry forward. Therefore, the BSI merger represents a viable option for the government to support the development of the Islamic banking sector, while competition within the industry remains dynamic. Based on our findings, we recommend that State-Owned Banks provide further support for the development of BSI, and that other conventional banks optimize their support for Islamic banks.